2016
DOI: 10.1007/s00168-016-0785-2
|View full text |Cite
|
Sign up to set email alerts
|

Economic performance, social progress and institutional reform in European neighbouring countries

Abstract: The objective of this article is to analyse the recent evolution of European Neighbouring countries (ENC) in different dimensions related to economic performance (measured in a broader sense), social progress and institutional reforms. With this aim, we design and build a composite indicator to measure these different dimensions. Next, the index is used to characterise the relative evolution of neighbouring countries compared to a wide sample of developed and developing economies. We also test whether a conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Accordingly, the quality of institutions stimulated by the EU's complex free trade agreements has positively affected trade in the EaP countries. This is also the view of López-Tamayo et al (2018), who admit the validity of the bilateral action plans and the positive effects of convergence with the EU in terms of enhancing the catch-up among the ENP countries. Our article builds on these findings and holds that the EU has had a significant impact on the EaP economies.…”
Section: Empirical Evidence On Convergence and Grow Th In Post-soviet Countriesmentioning
confidence: 72%
See 2 more Smart Citations
“…Accordingly, the quality of institutions stimulated by the EU's complex free trade agreements has positively affected trade in the EaP countries. This is also the view of López-Tamayo et al (2018), who admit the validity of the bilateral action plans and the positive effects of convergence with the EU in terms of enhancing the catch-up among the ENP countries. Our article builds on these findings and holds that the EU has had a significant impact on the EaP economies.…”
Section: Empirical Evidence On Convergence and Grow Th In Post-soviet Countriesmentioning
confidence: 72%
“…Provided the EaP and the CA countries were displaying a similar progress in reforms before the ENP creation (2.44 was the average transition score for the EaP countries during the first period, as compared to 2.31 within the CA), the difference grew after the ENP enforcement (3.06 within the EaP group, compared to 2.65 within the CA). Similarly, other studies also recognize the positive effects the ENP has had on the eastern neighbours, where the EU through its neighbourhood frameworks has managed to partially stimulate structural reforms and macro-policies, and also lifted trade barriers with the EaP states (López-Tamayo et al, 2018).…”
Section: Conflictsmentioning
confidence: 97%
See 1 more Smart Citation
“…The latter is also an issue for institutional research as evidenced by Schulz and Konig (2000) who found that institutional reform had a substantial impact on decision-making efficiency in terms of proposal-decision lag reduction. Several more instances of the post-integration Europe"s institutionalism described in Lopez-Tamayo, Ramos, and Surinach i Caralt (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The objective of the article by López-Tamayo et al (2016) is to analyse the recent evolution of the ENC by looking at GDP growth and also by considering different dimensions related to economic performance in a broader sense, particularly social progress and institutional reforms. The ENC performance along these different dimensions is compared with that experienced by a wide sample of economies including developed, developing, and emerging economies.…”
mentioning
confidence: 99%